2015
DOI: 10.3791/52566
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorod-assisted Optical Stimulation of Neuronal Cells

Abstract: Recent studies have demonstrated that nerves can be stimulated in a variety of ways by the transient heating associated with the absorption of infrared light by water in neuronal tissue. This technique holds great potential for replacing or complementing standard stimulation techniques, due to the potential for increased localization of the stimulus and minimization of mechanical contact with the tissue. However, optical approaches are limited by the inability of visible light to penetrate deep into tissues. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Illuminated by a pulsed laser at a resonant wavelength of 780 nm, these gold nanorods activated nearby neurons with a linear correlation to the duration of the laser pulse. It was also found that internalized gold nanorods promoted neurite outgrowth and induced a Ca 2+ influx in NG108-15 cells under continuous and pulsed irradiation respectively, both at a near-infrared resonant wavelength of 780 nm (Placement IV; Paviolo et al, 2013 , 2014a , 2015 ).…”
Section: Nanomaterial-enabled Optical Stimulationmentioning
confidence: 93%
See 2 more Smart Citations
“…Illuminated by a pulsed laser at a resonant wavelength of 780 nm, these gold nanorods activated nearby neurons with a linear correlation to the duration of the laser pulse. It was also found that internalized gold nanorods promoted neurite outgrowth and induced a Ca 2+ influx in NG108-15 cells under continuous and pulsed irradiation respectively, both at a near-infrared resonant wavelength of 780 nm (Placement IV; Paviolo et al, 2013 , 2014a , 2015 ).…”
Section: Nanomaterial-enabled Optical Stimulationmentioning
confidence: 93%
“…In order to generate localized heat to stimulate neurons, microparticles were used as optical absorbers to convert light to heat (Migliori et al, 2012 ; Farah et al, 2013 ). The opto-thermal transduction of gold nanomaterials due to localized surface plasmon resonance makes them particularly suitable as optical absorbers for neural stimulation (Figure 1C ; Paviolo et al, 2013 , 2014a , 2015 ; Eom et al, 2014 ; Yong et al, 2014 ; Yoo et al, 2014 ; Carvalho-de-Souza et al, 2015 ). Upon irradiation at the resonant frequency, electrons in gold nanomaterials oscillate and collide, generating and dissipating heat (Roper et al, 2007 ; Cao et al, 2014 ).…”
Section: Nanomaterial-enabled Optical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing PNFs is considered an innovative approach for modulating cellular activity based on cell-plasmon or cell-surface interaction [9,22,23,29,30,31,32,33,34,35,36]. Past in vitro experiments have exposed cells to a plasmonic nanomaterial dispersed in the cell culture medium or to a plasmonic nanomaterial deposited as 2D structures.…”
Section: Plasmonic Nanofactors As Neural Simulatorsmentioning
confidence: 99%
“…Looking at nature, the nanoscale ion channels are the driving forces behind the great diversity of neuronal dynamics, which provide biomimetic inspiration to overcome this trade-off by shrinking the electrode dimensions to the nanoscale. Although a variety of nanostructures, such as planar nanowires and suspended nanoparticles, [8][9][10][11][12][13] have been applied to neuronal recording and stimulation, a revolutionary breakthrough towards an organized and high-resolution neural interface has been enabled by 3D nanofabrication techniques. Vertical nanoelectrode arrays signicantly reduce the projection area on the planar substrate to which they are bound without compromising the interfacial area they share with the local cell membrane, allowing for the realization of high-density fabrication and parallel recording from different compartments of single neurons.…”
Section: Introductionmentioning
confidence: 99%